In vitro screening of plant resources for extra-nutritional attributes in ruminants : nuclear and related methodologies - Vercoe, Philip E.; Makkar, Harinder P. S.; Schlink, Anthony C. (Dordrecht ; London : Springer, 2010)
The aim of this manual is to provide a comprehensive guide to the methods involved in collecting, preparing and screening plants for bioactive properties for manipulating key ruminal fermentation pathways and against gastrointestinal pathogens. The manual will better equip the reader with methodological approaches to initiate screening programmes to test for bioactivity in native plants and find 'natural' alternatives to chemicals for manipulating ruminal fermentation and gut health. The manual provides isotopic and non-isotopic techniques to efficiently screen plants or plant parts for a rang.
-- Selecting Potential Woody Forage Plants That Contain Beneficial Bioactives -- Collecting, Processing and Storage of Plant Materials for Nutritional Analysis -- In Vitro Methods for the Primary Screening of Plant Products for Direct Activity against Ruminant Gastrointestinal Nematodes -- Assessing Antiprotozoal Agents -- Screening for Anti-proteolytic Compounds -- Screening for Compounds Enhancing Fibre Degradation -- In Vitro Screening of Feed Resources for Efficiency of Microbial Protein Synthesis -- Screening of Plants for Inhibitory Activity Against Pathogenic Microorganisms from the Gut of Livestock -- Screening Plants for the Antimicrobial Control of Lactic Acidosis in Ruminant Livestock -- Screening Plants and Plant Products for Methane Inhibitors -- Challenges in Extrapolating In Vitro Findings to In Vivo Evaluation of Plant Resources.
Includes bibliographical references and index.
Keywords: Ruminants -- Feeding and feeds; Ruminants -- Nutrition; Plants, Edible -- Testing; Ruminants; Animal Nutrition Sciences; Plants, Edible -- analysis